Workforce reorganization and the worker - Ben Kriechel; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2011)
In this paper we study the joint decision process of changing the structure of jobs and laying off individual workers in a firm that downsizes its workforce. A hierarchical decision model is proposed and estimated using personnel data from a firm in demise comparing the characteristics of the individual workers and the structure of the firm's labour force before and after its reorganization. Our results show that workers in jobs in the top levels of each skill group's hierarchy are better protected against downsizing due to larger productivity shocks and larger firing costs.
urn:nbn:de:101:1-201106224753
Keywords: J63; J65; L23; L60; L93; M51; 330; hierarchies; restructuring; control span; job displacement